HDI DETERMINANTS: FISCAL-DRIVEN, RGDP OR LOCAL LEADER’S COMMITMENT? (EVIDENCE FROM SOUTH KALIMANTAN PROVINCE) - Kamila, Nor (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Human Development Index (HDI) of South Kalimantan was ranked at 25 th among 34 provinces across Indonesia in 2016 and the score achieved below the national HDI result. The purpose of this research is to determine and analyze the effect of local fiscals (represented by locally-generated revenue (PAD), revenue sharing fund, general allocation fund (DAU), special allocation fund (DAK), personnel expenditure, goods expenditure, capital expenditure) local leader’s commitment, regional gross domestic product (RGDP)  and dependency ratio on HDI in the districts/cities within South Kalimantan. Population of this research are all districts/cities of South Kalimantan which consists of 13 regions in the period 2013-2016. Data analysis was conducted using double-log regression analysis. The research found that variable of locally-generated revenue and RGDP have positive effect on HDI, and variable of personnel expenditure, local leader’s commitment, and dependency ratio have negative effect on HDI. These results provide insightful findings to discuss. Local leaders’ commitment, for instance, did not contribute positively on HDI, it may be because their commitments are merely in the lip-service praxis.